IMPLEMENTATION OF ENVIRONMENTAL ACCOUNTING IN TOFU FACTORY WASTE MANAGEMENT: CASE STUDY OF DM93 TOFU FACTORY IN PALU CITY - Simanullang, Ratih; Sugianto, Sugianto; Usman, Ernawati; Mustamin, Mustamin (Accounting Studies and Tax Journal (COUNT), 2025)
Waste management in the tofu industry is an important aspect in maintaining business sustainability and environmental sustainability. Solid waste from tofu production can be reused, while liquid waste often becomes a source of pollution if not managed properly. Environmental accounting is an important tool in recording and measuring environmental costs associated with waste management, but its application in small industries is still limited. Method: This study uses a qualitative approach with a phenomenological method. Data were collected through interviews with factory owners, employees, and the surrounding community, as well as direct observation and analysis of financial report documents. Data analysis was carried out through data reduction, data presentation, triangulation, and drawing conclusions. Results: The results of the study indicate that the DM93 Tofu Factory has managed solid waste well by utilizing tofu dregs as animal feed. However, liquid waste management still faces challenges, especially in the effectiveness of the Wastewater Treatment Plant (WWTP). In addition, the application of environmental accounting is still very limited, where environmental costs are not explicitly recorded in the financial statements. The main challenges in implementing environmental accounting include the lack of understanding of business owners, the absence of regulations requiring the recording of environmental costs, and financial limitations for investment in waste management.